Preliminary Characterization of Melanin Isolated from Fruits and Seeds of Nyctanthes arbor-tristis (Journal of Scientific Research, 2009)
Melanin from Nyctanthes arbor-tristis fruits and seeds was isolated and purified by alkaline extraction, acid hydrolysis and organic solvents. Each, fruit and seed yielded melanin 50 mg/100g tissue weight. The melanins of fruit and seeds were analyzed by UV-visible and infrared (IR) spectroscopy for characterization. The IR spectrum of fruit and seed melanins did not match with each other and the seed melanin could be distinguished by their sharp peat at 285 nm from the fruit melanin in IR spectrum. Two melanins have shown absorptions above and below 1600 cm-1 in their respective IR spectrum. The melanins thus characterized were tested for their stability after incubating at different temperatures and in presence of oxidants (KMnO4 and K2Cr2O7) and metal ions (Mg++ and Zn++) for a specified period. The stability of the melanin was assessed by measuring changes in the absorbance at 285 nm. The results revealed that the fruit melanin was more stable at 50 ºC while the seed melanin was quite stable at 25 ºC. However, their stability was markedly affected by oxidants and metal ions.  Keywords: Melanin; Nyctanthes arbor-tristis; UV-visible spectroscopy; IR-spectroscopy; Oxidant. © 2009 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. DOI: 10.3329/jsr.v1i3.2005               J. Sci. Res. 1 (3), 655-661 (2009)